2013
DOI: 10.1179/1743282013y.0000000066
|View full text |Cite
|
Sign up to set email alerts
|

The double allopolyploidSphagnum×falcatulum(Sphagnaceae) in Tierra del Fuego, a Holantarctic perspective

Abstract: A Holantarctic species, the inter-subgeneric allopolyploid Sphagnum 6falcatulum s.l. is a cryptic species complex composed of allodiploid and allotriploid cytotypes. The allotriploid plants are double allopolyploids (one of just two reported for bryophytes), with the allodiploid cytotype being one parent. Using a combination of microsatellites, nucleotide sequences, and morphological characters, allotriploid S. 6falcatulum is shown to be the most widespread Sphagnum species in the Holantarctic, with geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
1
21
0
2
Order By: Relevance
“…Low levels or even a lack of genetic differentiation between plants on different continents occur in other bryophytes, including the Sphagnum species (see, e.g., Stenøien and S astad 1999;Thingsgaard 2001;Stenøien et al 2011). Some studies have shown a significant, yet weak, genetic differentiation between the intercontinental populations of peatmoss species (Stenøien and S astad 1999;Sz€ ov enyi et al 2008;Karlin et al 2013). Our results suggest that the North Atlantic Ocean is not an insurmountable barrier for gene flow in a S. warnstorfii metapopulation.…”
Section: Negligible Effects Of Geographymentioning
confidence: 51%
See 3 more Smart Citations
“…Low levels or even a lack of genetic differentiation between plants on different continents occur in other bryophytes, including the Sphagnum species (see, e.g., Stenøien and S astad 1999;Thingsgaard 2001;Stenøien et al 2011). Some studies have shown a significant, yet weak, genetic differentiation between the intercontinental populations of peatmoss species (Stenøien and S astad 1999;Sz€ ov enyi et al 2008;Karlin et al 2013). Our results suggest that the North Atlantic Ocean is not an insurmountable barrier for gene flow in a S. warnstorfii metapopulation.…”
Section: Negligible Effects Of Geographymentioning
confidence: 51%
“…; Karlin et al. ). Our results suggest that the North Atlantic Ocean is not an insurmountable barrier for gene flow in a S. warnstorfii metapopulation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Aunque su presencia se ha documentado para otros sectores de la ecorregión subantártica de Magallanes (Díaz et al 2005), S. falcatulum está pobremente registrado en la Isla Navarino, detectado el año 2013 en la zona de Puerto Toro (al Este) a un costado de un camino vehicular e ingresada a la colección del New York Botanical Garden (http://sweetgum.nybg.org/ science/vh/). De acuerdo con Karlin et al (2013), S. falcatulum es la especie de Sphagnum más ampliamente distribuida en el Holoantártico (que incluye el continente Antártico, la Tierra del Fuego, la ecorregión subantártica de Magallanes, Nueva Zelanda, y las islas del océano Antártico al sur de los 40º latitud). La singularidad del hábitat donde registramos a S. falcatulum -ilustrado en las fotografías de la Figs.…”
unclassified